2008
DOI: 10.1038/sj.bjp.0707452
|View full text |Cite
|
Sign up to set email alerts
|

Thiazolidinediones: effects on insulin resistance and the cardiovascular system

Abstract: Thiazolidinediones (TZDs) have been used for the treatment of hyperglycaemia in type 2 diabetes for the past 10 years. They may delay the development of type 2 diabetes in individuals at high risk of developing the condition, and have been shown to have potentially beneficial effects on cardiovascular risk factors. TZDs act as agonists of peroxisome proliferator‐activated receptor‐γ (PPAR‐γ) primarily in adipose tissue. PPAR‐γ receptor activation by TZDs improves insulin sensitivity by promoting fatty acid upt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(88 citation statements)
references
References 123 publications
1
86
0
1
Order By: Relevance
“…It has attracted much attention as a regulator of metabolic status and target for the thiazolidinedione drugs that are licensed for use in the treatment of type-2 diabetes and include rosiglitazone and pioglitazone (Quinn et al, 2008). Like TRP channels, PPAR-␥ has promiscuous sensitivity to a range of ligands (Kliewer et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It has attracted much attention as a regulator of metabolic status and target for the thiazolidinedione drugs that are licensed for use in the treatment of type-2 diabetes and include rosiglitazone and pioglitazone (Quinn et al, 2008). Like TRP channels, PPAR-␥ has promiscuous sensitivity to a range of ligands (Kliewer et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…TZDs are selective and potent agonists for the peroxisome proliferatoractivated receptor (PPAR)g, and influence the transcription of genes that regulate lipid and glucose metabolism (8). Recent data suggest that PPARg agonists also may modulate other biological processes that are involved in atherosclerosis, including inflammation (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…3 The mechanisms of TZD action are still being investigated but it has been clearly demonstrated that some of their effects are mediated through activation of the peroxisome proliferator-activated receptor-c (PPARc), a member of the nuclear receptor superfamily of ligand-dependent transcription factors predominantly expressed in adipocytes but also in other normal and transformed cells. 4 Beyond the metabolic actions, several studies indicate that TZD may have also anticancer properties in a variety of different epithelial malignancies.…”
mentioning
confidence: 99%